2010
DOI: 10.1159/000267865
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of ADAM10 Inhibitor GI254023X

Abstract: Background: The metalloproteinases ADAM10 and ADAM17 are involved in various diseases: neurodegeneration, cancer and inflammation. Objective: The inhibition of these proteases is a promising target in the treatment of inflammation and cancer. Methods and Results: In this study, we present an improved synthesis of the ADAM10 reference inhibitor GI254023X with a higher overall yield, enhanced detection ability and increased acid stability, providing easier handling. Conclusion: This upscaled synthesis, free of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…4E). The involvement of ADAM10 was further confirmed using the specific ADAM10 inhibitor GI254023X (36), which affected MICB release in a dose-dependent manner in both untreated and drugtreated MM cells (Fig. 4F).…”
Section: Adam10 Is Involved In Drug-induced Micb Release From MM Cellsmentioning
confidence: 68%
“…4E). The involvement of ADAM10 was further confirmed using the specific ADAM10 inhibitor GI254023X (36), which affected MICB release in a dose-dependent manner in both untreated and drugtreated MM cells (Fig. 4F).…”
Section: Adam10 Is Involved In Drug-induced Micb Release From MM Cellsmentioning
confidence: 68%
“…M ␤ CD, zaragozic acid A (ZA), mevalonate, lovastatin, fl uvastatin, and atorvastatin were from Sigma-Aldrich (Germany). The inhibitor GM6001 (broadspectrum metalloproteinase inhibitor) was from Calbiochem and GI254023X (a preferential ADAM10 inhibitor) was a kind gift from B. Schmidt (University Darmstadt, Germany) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…1C), indicating that the survival of oocytes was not affected by inhibiting ADAM10. In addition, we cultured ovaries with another ADAM10 selective inhibitor GI254023X (Hoettecke et al, 2010;Hundhausen et al, 2003;Lo Sardo et al, 2012). The results showed that 7 days of GI254023X treatment also significantly decreased the number of follicles (1138.0±184.0 per ovary for GI254023X versus 8188.0±1152.3 per ovary for control; Fig.…”
Section: Suppressing Adam10 Disrupts Germline Cyst Breakdown and Primmentioning
confidence: 88%